Synthesis of Silver Nanoparticles from Extract of Epiphytic Shrub Leaves (Ficus heteropleura Blume) on Oil Palm Plant and Evaluation of Their Antibacterial Activity Against Escherichia coli - Tri Adinda Rati; Fitra Perdana; Prasetya Prasetya (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
Silver nanoparticles are silver metal particles with a size of less than 100 nm. Extract of epiphytic shrub leaves (Ficus heteropleura Blume) serves as a bioreductant in producing silver nanoparticles, which are utilized for their antibacterial properties against Escherichia coli. This study aims to synthesize silver nanoparticles and assess their activity against Escherichia coli. Silver nanoparticles (AgNPs) were synthesized using the green synthesis method with Ficus heteropleura leaf extract with silver nitrate (AgNO3). AgNPs were synthesized using a 1 mM solution of AgNO3 and different concentrations (2, 4, 6, 8, and 10%) of Ficus heteropleura extract. The AgNPs were characterized using UV-Vis spectrophotometer, FTIR, and PSA. UV-Vis analysis revealed that AgNPs at concentrations ranging from 2% to 10% exhibited absorbance peaks within the wavelength range of 201.2–473.5 nm. FTIR analysis identified functional groups such as OH, CH, C=C, C≡C, C≡N, and CO, which played a role in reducing silver nanoparticles. The size distribution of AgNPs was determined, with AgNPs synthesized at a concentration of 6% exhibiting a size range of 1–100 nm, constituting 40.77% of the total. For AgNPs synthesized at concentrations of 8% and 10%, the percentage of nanoparticles in the 1–100 nm size range was found to be 26.845% and 1.28%, respectively. The antibacterial activity of AgNPs at concentrations of 6% and 8% against Escherichia coli demonstrated moderate effectiveness.